2023
DOI: 10.4314/sajas.v53i1.01
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cardiac troponin I (cTnI), T (cTnT), and some biochemical parameters in Arabian racehorses after training

Abstract: The aim of this study was to compare the changes in the content of cTnI, cTnT and some biochemical parameters (CK–MB, LDH, AST, ALT) in Arabian racehorses before and after training. Diagnosis of myocardial disease in horses is very difficult due to the lack of specific cardiac signs. Cardiac diseases are seen as a cause of sudden death or decreased performance in horses. It has also been reported that excessive exercise may cause transient myocardial damage. In our study, 20 healthy stallion Arabian racehorses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…In a study by Ayvazoğlu et al. ( 2023 ) on Arabian racehorses, biochemical data were taken before and after a 30‐min training session. They reported pre‐training levels of creatine phosphokinase (CK‐MB), lactate dehyrogenase (LDH), aspartat aminotransferase (AST) and Alanin Amimotransferase (ALT) as 231.15 ± 8.96, 692.45 ± 34.12, 309.92 ± 18.48 and 11.83 ± 0.92 U/L, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ayvazoğlu et al. ( 2023 ) on Arabian racehorses, biochemical data were taken before and after a 30‐min training session. They reported pre‐training levels of creatine phosphokinase (CK‐MB), lactate dehyrogenase (LDH), aspartat aminotransferase (AST) and Alanin Amimotransferase (ALT) as 231.15 ± 8.96, 692.45 ± 34.12, 309.92 ± 18.48 and 11.83 ± 0.92 U/L, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on endurance horses [26][27][28] reported an increase in cTnI levels after endurance rides, while Fazio et al [29] found cTnI increases after jump training in healthy horses. Ayvazoglu et al [30] and Pourmohammad et al [31] found cTnI increases in Arabian and thoroughbred racehorses after training. In the context of racehorses, Rossi et al [32] demonstrated that increased cTnI concentrations and cardiac arrhythmias after racing indicate myocardial damage.…”
Section: Introductionmentioning
confidence: 99%